Essays on behavioral responses to development interventions - Emerick, Kyle Jared (ProQuest Dissertations & Theses, 2014)
This dissertation combines three papers which are all empirical analyses of agricultural interventions in developing countries. I focus on how new policies, technologies, and institutions affect the behavior of small-scale farmers in both Mexico and India. The first paper focuses on the certification of agricultural land in Mexico while the second and third papers focus on technology adoption in rural India. Chapter 1, which is based on joint work with Alain de Janvry, Marco Gonzalez-Navarro, and Elisabeth Sadoulet, shows that removing the link between active land use and ownership through certification leads to a reallocation of labor away from agriculture and towards migration. In particular, we use the rollout of the Mexican land certification program from 1993 to 2006 to show that households obtaining land certificates were subsequently 28% more likely to have a migrant member. This response was differentiated by initial land endowments, land quality, outside wages, and initial land security, as predicted by our model. Effects on land under cultivation were heterogeneous: in high land quality regions land under cultivation increased while in low quality ones it declined. Chapter 2, which is based on joint work with Alain de Janvry, Elisabeth Sadoulet, and Manzoor Dar, shows evidence that risk is an important factor that constrains the decisions made by small farmers. More specifically, the chapter reports results of a field experiment in Odisha India that quantifies the effects of Swarna-Sub1, a promising new rice seed that effectively reduces risk by sharply reducing the susceptibility of the crop to flood damage. In doing so, the chapter offers novel evidence on the effect of a direct reduction in production risk on economic behavior. Specifically, access to this new technology leads to increases in area cultivated, fertilizer used, and the likelihood of using a more modern planting method. Also, the technology reduces precautionary savings of grain for consumption and increases the use of agricultural credit. An important implication from the chapter is that technological progress that directly eliminates weather-induced production variability offers a promising method of advancing agriculture in areas that are prone to extreme weather. Chapter 3 builds on the promising results in Chapter 2 by studying diffusion of Swarna-Sub1. I provide an experimental test of whether informal exchange of Swarna-Sub1 between farmers produces an efficient allocation. I report results on a field experiment, also in Odisha, to compare decentralized trade of Swarna-Sub1 through networks with an approach where demand was revealed via door-to-door sales. While 84% of farmers are expected to gain from Swarna-Sub1, only 7% adopt in networks. Conversely, 40% of farmers adopt when demand is revealed in door-to-door sales. Using variation across the sample in estimated gains in revenue, I show that 63% of the gains from door-to-door sales are lost with decentralized trade through networks. Frictions preventing interactions between farmers from different social groups offer an explanation for the results. Sub-caste and surname association with suppliers are strong predictors of adoption in networks, but have no effect in door-to-door sales. The main implication from the chapter is that relying on exchanges between farmers to disseminate new seed varieties will not produce an allocation where demand is met.